Bertie: just like daddy - Pfister, Marcus (NorthSouth, 2009)
Bertie wants to be just like Daddy and drink coffee, shave, and use a credit card, but all he ever hears is "When you're bigger..." or "when you grow up...". At last the tables are turned when Bertie plays with his trains, and Daddy wants to be just like Bertie.